Kepemimpinan dan Kepercayaan - Annysa Gea Putri; Dinda Nurul Wahidiyah; Fitria Ghaida Nurrahma (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
ABSTRAK In the same context, leadership and trust are related in an organization or activity. Having trust in leaders has a positive impact on results such as good behavior as well as job satisfaction and engagement. Leadership refers to a person's way of leading, directing and managing the stages of an organization to achieve a predetermined goal. In the context of this research, we use Visionary and Transformational leadership methods where as a leader develops his vision in leading to provide good direction and as a transformational leader he needs to be aware of change and must create a new vision and implement changes to that vision. Leadership and trust have factors that support building positive relationships, namely freedom from fear, communication, interaction, personal involvement, and honesty. This research uses Visionary and Transformational leadership methods where developing a vision as a leader in leading to provide good direction and as a transformational leader needs to be aware of change and must create a new vision and implement changes with a clear vision and mission regarding the future of the organization or a group that can direct actions to achieve goals